An activity-oriented web application for fresh produce traceability. (6th May 2010) - Manikas, Ioannis; Manos, Basil; Vlachopoulou, Maro; Manthou, Vassiliki
The successful control of the physical flow of the products along the supply chain and product safety assurance depends on the existence of an efficient traceability system. This system must be able to identify each and every single unit produced and distributed from farm to fork. In this paper we present a web-based application that enables quality, origin and processing-related data entry in real time. The application's theoretical background lies on the Traceability Data Pool (TDP) model described in the literature and aims to offer a practical solution for traceability support, especially for the stakeholder operating in the supply chain base, such as the farmers and agricultural cooperatives. This activity-oriented web application connects field treatments with the rest of the supply chain without implementing additional physical labelling. This application aims at integrating the existent labelling systems implemented in different levels of the supply chain, under a common standard virtual crop codification following the produce along the supply chain, from farm to fork, thus achieving total traceability.